Enteric Methane Emissions and Rumen Fermentation Profile Treated by Dietary Chitosan: A Meta-Analysis of In Vitro Experiments - R. P. Harahap; D. Setiawan; Nahrowi Nahrowi; S. Suharti; T. Obitsu; A. Jayanegara (Tropical Animal Science Journal, 2020)
Chitosan is a natural compound obtained from deacetylation of chitin, which is a biopolymer present in the exoskeleton of crustaceans such as crabs and shrimp. The present study aimed to perform a meta-analysis from published studies regarding the effects of chitosan on methane emission and rumen fermentation profile of in vitro batch culture experiments. A total of 41 studies from 12 articles were integrated into a database. Parameters included were gas production, methane emission, rumen fermentation characteristics, microbial population, nutrient digestibility, and fatty acid profile. Data were analyzed according to mixed model methodology in which different studies were treated as random effects and chitosan addition levels were treated as fixed effects. Results showed that chitosan addition was able to reduce enteric methane emissions (p<0.001). Such methane decrease was accompanied by a decline in the protozoa population (p<0.05) and a tendency of methanogen reduction (p<0.1). The increasing chitosan level was associated with a decrease in total VFA and ammonia concentrations (both at p<0.001). Chitosan addition decreased acetate proportion (p<0.001) while elevated propionate proportion (p<0.001). Chitosan was associated with an increase of dry matter digestibility, crude protein digestibility, and neutral detergent fiber digestibility (p<0.001). Chitosan increased concentrations of C18:3n3 (p<0.05), conjugated linoleic acid (p<0.01) and polyunsaturated fatty acids (p<0.01) while decreased concentration of saturated fatty acids (p<0.001). It can be concluded that chitosan addition can mitigate enteric methane emission and alters rumen fermentation profiles in a favorable direction.